The Effect of Transformational Leadership and Work Motivation on Employee Job Satisfaction in The Sewing Department of PT. Adis Dimension Footwear - Septianingtyas, Luhfi; Purwanto, Agus; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the simultaneous influence of transformational leadership and work motivation on job satisfaction among sewing department employees at PT. Adis Dimension Footwear, Balaraja, Tangerang. This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all sewing department employees at PT. Adis Dimension Footwear, Balaraja, Tangerang. The sample size was 56 respondents. Simple random sampling was used to determine the sample size. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis using SPSS 26.The results of this study indicate that (1) partially, transformational leadership significantly influences t-test on job satisfaction among sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.044>2.006) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work motivation significantly influences the job satisfaction of Sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (9.062>2.006) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and work motivation significantly influence the job satisfaction of Sewing department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated F value> F table (66.089>3.17) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that transformational leadership and work motivation, both partially and simultaneously, have a significant influence on employee job satisfaction in the sewing department at PT. Adis Dimension Footwear, Balaraja, Tangerang.